Antidiabetic Activity of Hot Tea Infusion of Leaves of Moringa stenopetala in Streptozotocin-Induced Diabetic Rats - Toma A (Dove Medical Press, 2022)
Alemayehu Toma Department of Pharmacology, Hawassa University, Hawassa, EthiopiaCorrespondence: Alemayehu Toma, Tel +251913259141, Email alemayehutoma@gmail.comBackground: Moringa stenopetala is a traditionally used medicinal plant that has been used for the management of different disorders including diabetes in Ethiopia. This study was aimed to assess the antidiabetic activity of hot tea infusion of leaves of Moringa stenopetala in streptozotocin-induced diabetic rats.Methods: Experimental animals were Wistar male rats aged 4- 6 weeks weighing 200- 250 gram. The animals were maintained in equal light/dark series of laboratory conditions, and the average ambient temperature was 23± 2 °C. The hot tea infusion of Moringa stenopetala leaves of different concentrations (as fine and coarse powder decoction), distilled water (10 mL/kg), and 150 mg/kg body weight of metformin were administered to diabetic rats as test, negative control, and positive standard drugs, respectively. Sucrose oral challenge test was also carried out to assess the effect of Moringa stenopetala hot tea infusion on postprandial glucose level. Blood glucose level was measured at 0, 30, 60, 90, and 180 minutes. Statistical analysis was conducted by SPSS package version 23, and the p-value less than 0.05 was declared as level of statistical significance.Results: The phytoconstituents that tested positive in hot tea infusion of Moringa stenopetala leaves were alkaloids, tannins, flavonoids, saponins, and terpenoids. Different experimental groups treated with the hot tea infusion of Moringa stenopetala leaves showed significant reduction of blood glucose level after 30 minutes of hot tea infusion administration. In addition, the hot tea infusion at a different concentration for both fine and coarse powders reduced significantly raised blood glucose level. The present findings revealed that the hot tea infusion has blood glucose-lowering and antioxidant effects with wide safety margin.Conclusion: The findings indicated that the hot tea infusion of the leaves of Moringa stenopetala shows a credible reduction in blood glucose level in rats.Keywords: Moringa stenopetala leaves, blood glucose, antioxidant, antidiabetic activity, hot tea infusion